2021
DOI: 10.3390/pharmaceutics13111923
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Cyclodextrins and Amino Acids for the Development of Cefixime Oral Solutions for Pediatric Use

Abstract: Cefixime (CEF) is a cephalosporin included in the WHO Model List of Essential Medicines for Children. Liquid formulations are considered the best choice for pediatric use, due to their great ease of administration and dose-adaptability. Owing to its very low aqueous solubility and poor stability, CEF is only available as a powder for oral suspensions, which can lead to reduced compliance by children, due to its unpleasant texture and taste, and possible non-homogeneous dosage. The aim of this work was to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The drug concentration to be loaded was determined considering its solubility in the formulation (see Section 3.1) and its minimum inhibitory concentration (MIC) necessary to exploit its antimicrobial activity. In a previous study [42], we found that the MIC of CEF against Escherichia coli is <0.5 µg/mL. Thus, even the lowest drug concentration used for NLCs loading (0.1 mg/mL) was more than 20 folds higher than its MIC value.…”
Section: Preparation and Characterization Of Nlcsmentioning
confidence: 85%
“…The drug concentration to be loaded was determined considering its solubility in the formulation (see Section 3.1) and its minimum inhibitory concentration (MIC) necessary to exploit its antimicrobial activity. In a previous study [42], we found that the MIC of CEF against Escherichia coli is <0.5 µg/mL. Thus, even the lowest drug concentration used for NLCs loading (0.1 mg/mL) was more than 20 folds higher than its MIC value.…”
Section: Preparation and Characterization Of Nlcsmentioning
confidence: 85%
“…One limitation of this study is that the human taste panel was conducted in healthy adults rather than children (who represent the target population) for a subsequent extrapolation of the results. As it is mentioned, for ethical reasons, conducting a clinical trial in children is quite complex [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, authorities recommend conducting palatability assessments involving children whenever feasible. When such assessments with children are not possible, taste screening by adult panels can serve as an alternative method, with the results examined for their applicability to children [ 19 ]. At this stage of development, we deemed an initial screening by an adult testing panel to be acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…This me the covalent bonding structure has to be explicitly known before starting the sim however, most researchers perform their MD studies only with the neutral, nonform of the drug, which consequently limits the applicability of the obtained re pure aqueous, non-buffered solutions. A noteworthy exception was the recent w Cirri et al [13], who observed that the potential energies of the interaction betwe β-CD and cefixime differ by 75 kJ/mol (17.9 kcal/mol) depending on whether the…”
Section: Peer Reviewmentioning
confidence: 99%